Influência da alimentação sobre os níveis de retinol no leite caprino - Melo, Ciro Uchoa de (2005)
The caprine milk is a product of high biological value and high digestibility. Due to these characteristics it is quite used by newly born children that are not breastfed or that are intolerant to the bovine milk. The vitamin deficiency is a public health problem in underdeveloped areas as the Northeast of Brazil and where areas the caprine ones adapt very well. The present study was led to analyze the influence of the feeding in the vitamin levels in the caprine milk. The animals used were the races Saanen and Murciana, divided in three groups. The first group with 38 animals of race Saanen and the second with 30 animals of race Murciana were, fed with concentrated and voluminous. A third group with 20 animals of the race Saanen was fed exclusively with voluminous. The four group was added with 10. 000 UI of retinol palmitato, administered directly, like capsule, in the mouth of animal. Parallel it was verified the level of retinol of milk in the beginning and final of the sucked, in the goats of the second group (race Murciana n =30). The retinol of caprine milk was determined through the system of liquid cromatografia of high efficiency (HPLC). The retinol levels in the studied groups were respectively: first (38. 5 ± 12. 7 μg/100ml), second (40. 5 ± 9. 7 μg/100ml); third, with 20 animals of race Saanen fed exclusively with voluminous (23. 1 ± 6. 7 μg/100ml) and in the group a, suplementation with 10. 000 UI of retinol palmitato (43,7 ± 18,8 μg/100ml) before, and (61,9 ± 26,9 μg/100ml) after the supplementation. It was not found significant difference between the averages from animals of the first and second group, that were fed with the same concentrate diet and voluminous, showing that the retinol levels in the milk of these two races are equivalent. Already in the animals of the first and third group that they were fed with different diets, in those which diet was just voluminous, a drastic reduction was verified in the retinol levels. In relation to the retinol of the milk in different moments from the same sucked, it was observed in the beginning of the breast-feeding (22. 6 ± 9. 8 μg/100ml) and at the end of the sucked (49. 6 ± 14. 7μg/100ml), being the difference between the averages, statistically significant (p < 0,0001). Already in the animals that were supplemented, a significant increase was observed in the retinol concentration, being obtained a medium response of 41,85%